Principles of tissue engineering - Lanza, R. P. (Robert Paul) 1956-; Langer, Robert S.; Vacanti, Joseph; Atala, Anthony 1958- (Elsevier/Academic Press, 2020)
Now in its fifth edition, Principles of Tissue Engineering has been the definite resource in the field of tissue engineering for more than a decade. The fifth edition provides an update on this rapidly progressing field, combining the prerequisites for a general understanding of tissue growth and development, the tools and theoretical information needed to design tissues and organs, as well as a presentation by the world's experts of what is currently known about each specific organ system. As in previous editions, this book creates a comprehensive work that strikes a balance among the diversity of subjects that are related to tissue engineering, including biology, chemistry, material science, and engineering, among others, while also emphasizing those research areas that are likely to be of clinical value in the future. This edition includes greatly expanded focus on stem cells, including induced pluripotent stem (iPS) cells, stem cell niches, and blood components from stem cells. This research has already produced applications in disease modeling, toxicity testing, drug development, and clinical therapies. This up-to-date coverage of stem cell biology and the application of tissue-engineering techniques for food production - is complemented by a series of new and updated chapters on recent clinical experience in applying tissue engineering, as well as a new section on the emerging technologies in the field.